Performing Arts, New Technologies, Museum Heritage and its Application as a Tool for Social Change with a Group of Victims of Violence and Sexual Explotation - Cernuda-Lago, Amador (Eikón / Imago, 2019)
This article studies the benefits of Art in clinical and social intervention through proposals of heritage artistic education in museums, scenic art activities, cognitive psychotherapy with support in new technologies such as virtual reality. Method: 34 women, victims of exploitation and sexual violence, were interviewed clinically and evaluated with psychological tests. 48 sessions of psychoballet and scenic art therapy, 8 guided visits to art and ethnology museums and 24 sessions of new technologies to support cognitive psychotherapy and heritage artistic awareness. Results: anxiety decreased 40%, increasing self-esteem 35%. Conclusions: intervention through the arts has allowed an innovation in alternative recovery to the word.